FACTORS ASSOCIATED WITH THE PREVALENCE OF SARCOPENIA IN ELDERLY UNIVERSITY WORKERS - Ronald Winardi Kartika; Yosephin Sri Susanti; Susanti Dewi Winata (JURNAL WIDYA MEDIKA, 2023)
The most common cause of sarcopenia is a lack of physical activity throughout the day. In addition, there are also other possibilities that could be the cause of this loss of muscle mass, namely: Decreased levels of certain hormones related to muscle. University workers who experience retirement often experience sarcopenia, because when they are still active, university workers are less active and have less protein intake. For this reason, it is necessary to pay attention to the activities of university workers while they are still active and productive at work